Medical communications: principles and best practice - Polson, Hannah (Henry Stewart Talks, 2019)
Overview: what is ‘medical communications’, Understanding your audience (scientific community, regulatory authorities, payers, doctors, nurses, patients and PAGs, pharmaceutical companies), Finding out what there is to know and where the information is coming from, Possible channels to provide the information to our audience, Why we do what we do